Reconstructing glacier-based climates of LGM Europe and Russia – Part 2: A dataset of LGM precipitation/temperature relations derived from degree-day modelling of palaeo glaciers - R. Allen; M. J. Siegert; A. J. Payne (Copernicus Publications, 2008)
The study of European and Russian Quaternary glacial-geological evidence during the last 15 years has generated sufficient data to use former glacial extent as a proxy for Last Glacial Maximum (LGM) climate (precipitation and temperature) at a continental scale. Utilisation of such data is relevant for two reasons. First, continental to global scale proxy reconstructions of past climate are an important tool in the assessment of retrospective general circulation model (GCM) simulations. Second, the development of a multi-proxy approach will result in a more robust proxy based climate signal. A new and independent dataset of 36 LGM precipitation and temperature relationships derived from European and Russian mountain regions is presented in this paper. A simple glacier-climate model was used to establish the optimum LGM precipitation/temperature conditions for each region from a suite of over 4000 model climates using the principle of zero cumulative mass balance. Clear regional trends are present in the reconstructed LGM precipitation and temperature curves; assuming present precipitation temperature anomalies north of the Alps are 2°C and 5°C larger than those in the western and eastern Mediterranean, respectively. In Russia the model results suggest that the climates in both the Arctic Urals and Puterana Plateau were probably conducive to the existence of small mountain glaciers at the LGM.